Self-Incompatibility Triggers Irreversible Oxidative Modification of Proteins in Incompatible Pollen . Issue 3 (22nd April 2020) - Haque, Tamanna; Eaves, Deborah J.; Lin, Zongcheng; Zampronio, Cleidiane G.; Cooper, Helen J.; Bosch, Maurice; Smirnoff, Nicholas; Franklin-Tong, Vernonica E.
Abstract : In the self-incompatibility response, incompatible pollen stimulates irreversible oxidative protein modifications that affect crucial protein functions. Abstract: Self-incompatibility (SI) is used by many angiosperms to prevent self-fertilization and inbreeding. In common poppy ( Papaver rhoeas ), interaction of cognate pollen and pistil S -determinants triggers programmed cell death (PCD) of incompatible pollen. We previously identified that reactive oxygen species (ROS) signal to SI-PCD. ROS-induced oxidative posttranslational modifications (oxPTMs) can regulate protein structure and function. Here, we have identified and mapped oxPTMs triggered by SI in incompatible pollen. Notably, SI-induced pollen had numerous irreversible oxidative modifications, while untreated pollen had virtually none. Our data provide a valuable analysis of the protein targets of ROS in the context of SI-induction and comprise a benchmark because currently there are few reports of irreversible oxPTMs in plants. Strikingly, cytoskeletal proteins and enzymes involved in energy metabolism are a prominent target of ROS. Oxidative modifications to a phosphomimic form of a pyrophosphatase result in a reduction of its activity. Therefore, our results demonstrate irreversible oxidation of pollen proteins during SI and provide evidence that this modification can affect protein function. We suggest that this reduction in cellular activity could lead to PCD.